Integrated metabolome-transcriptome analyses reveal key pathways regulating staminate catkin development and pollen maturation in Betula platyphylla - Liu, Xinying; Shi, Jiayuan; Zhang, Jingyun; Jakada, Bello Hassan; Guo, HuiLing; Zeng, Kehao; Lan, Xingguo (Frontiers in Plant Science, 2025)
IntroductionFlavonoids are the major metabolites in Betula platyphylla. However, our understanding of the role that flavonoids play in staminate catkin development and pollen maturation is still limited.Methods and resultsHere, we performed a metabolome analysis during staminate catkin development and pollen maturation in B. platyphylla. These results indicated that mature pollen exhibited significantly high concentrations and diverse profiles of flavonoids. Moreover, using the integrated transcriptomic and metabolomic analyses, we found major metabolites and key genes involved in staminate catkin development and pollen maturation in the flavonoid pathway. Furthermore, WGCNA analysis identified key transcription factors (BpMYB18, BpMYB72, BpMYB95, and BpMYB109) as potential regulators in the flavonoid pathway.DiscussionThese findings shed light into the metabolic pathways regulating the development of staminate catkins and pollen maturation in B. platyphylla.